Investigation of flow and heat transfer at the surface of a single circular cooling fin - Z Sapozhnikov, S; Y Mityakov, V; V Mityakov, A; A Gusakov, A; A Grekov, M; V Seroshtanov, V (International Journal of Engineering and Technology, 2018)
All heat transfer processes are connected with flow structure. It is important to know both heat transfer and flow characteristics. For the first time it is proposed to connect Particle Image Velocimetry (PIV) method with gradient heat flux measurement and thermal imaging for complex study of hydrodynamics and heat transfer at the surface of a single circular cooling fin. The hollow fin is heated with saturated water steam; meanwhile its isothermal external surface simulates the ideal fin. Flow and heat transfer at the surface of the solid fin of the same size and shape, and made of titanium alloy is investigated in the same regimes. Gradient Heat Flux Sensors (GHFS) were installed at different places of the fin surface. Velocity field near the fin, temperature field at the surface of the fin and heat flux were obtained. Comprehensive method including heat flux measurement, PIV and thermal imaging allows to study the flow and heat transfer at the surface of the fin in real time regime. The possibility of complex study of flow and heat transfer for non-isothermal fins is shown.Â